La sociologie de l'engagement politique : le Mahdawîya indien et l'État - Derryl N. MacLean (Revue des Mondes Musulmans et de la Méditerranée)
This paper examines the interpretative capacity and political volatility of the Mahdawîya movement founded by Sayyid Muhammad Jaunpûrî (1443-1505) which spread widely across South Asia. The movement's engagement with the Mughal state, it is argued, varied with social location, moving from jihad activism to hijra communal withdrawal, a process requiring continual reinterpretation of texts. The paper challenges the notion that Mahdism, unlike other millennialisms, must necessarily engage in activist jihâd against the state, a perspective rooted in Orientalist assumptions concerning the importance of the state and the primacy to Muslim action of Islâmic formative texts.